Temperature and Photoperiod Control of Shoot Growth and Floral Bud Initiation in Biennial-Fruiting Blackberries - Anita Sønsteby; Mirjana Sadojevic; Ola M. Heide (Horticulturae)
Growth and flower bud initiation (FBI) were studied in single-stem plants of four biennial-fruiting cultivars in a controlled environment and under field conditions at 60°40′ N. Shoot growth varied widely among the cultivars but was significantly enhanced by high temperature (20 °C) in all cultivars, whereas photoperiod had a subordinate growth effect. FBI data from bud dissection after 6 weeks of cultivation in the phytotron were used to calculate FBI indices for the various cultivars and environment conditions. The indices also varied much among the cultivars but were enhanced by elevated temperature, being highest in ‘Natchez’ and ‘Sweet Royalla’, while ‘Natchez’ was the only cultivar in which FBI was significantly enhanced by short days. The non-vigorous and erect growing ‘Ouachita’ remained vegetative at both temperatures but flowered in spring after overwintering at 0.5 °C. The field experiment confirmed the superior growth vigor of ‘Loch Ness’ and ‘Sweet Royalla’ as well as the photoperiodic sensitivity of ‘Natchez’. The results also confirmed that floral initiation starts in lateral buds located 10–20 nodes below the apex, and from there it progresses in both acropetal and basipetal direction. We conclude that temperature is at least as important as the photoperiod for the control of FBI in biennial-fruiting blackberries.